(untitled) (Colombia Medica, 2023)
Introduction: The school population represents a fundamental group for health promotion actions, given that the foundations of healthy behaviors in adult life are established in children and adolescents, whom the school can greatly influence. Objective: To describe the health-related behavioral factors of schoolchildren between 13 and 17 years of age in secondary and middle school in Colombia. Methods: A national cross-sectional study was conducted (i.e., School Health Survey -ENSE-) that recorded information on dietary practices, physical activity, alcohol and drug consumption, injuries and bullying, and oral, visual and hearing health. Sampling was probabilistic, cluster and multistage. Results: Schoolchildren have low consumption of fruits, vegetables (13.1%) and dairy (76.5 %), high consumption of ultra-processed foods (82.4 %), sugary drinks (74.0 %) and fast foods (14.8 %), frequent addition of salt at the table (43.3 %), low compliance with physical activity recommendations (15.0 %) and high sedentary lifestyle (46.3 %), frequent consumption of alcohol (44.7 %) and psychoactive substances (14.7 %), in addition to prevalent situations of bullying (15.4 %), rejection (8.2 %) and verbal aggression (42.7 %). Conclusions: The ENSE shows critical inequalities by gender, ethnicity and social class throughout the country. The indicators observed in schoolchildren are precursors of various chronic and degenerative diseases and mental illness, which requires the urgent attention of the different social actors in the country.